Systematic Review: Forms of Family Involvement in Post School Transition Program Planning for Students with Disabilities - Safari, Muhammad Bakhtiar (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2025)
This study explores the role of family involvement in the planning and implementation of post-school transition programs for students with disabilities through a systematic literature review (SLR) using a qualitative approach. Data were obtained from three databases: ScienceDirect, Scopus, and ERIC Journal. The results of the study show that family involvement focuses on decision-making, emotional support, and collaboration with education professionals. Active parental involvement in decision-making has been shown to improve students' readiness for further education or the workforce. Emotional support in the form of motivation, stress management, positive communication, and a stable home environment helps students navigate the transition period with confidence. Communication barriers between families and professionals remain a major challenge that can hinder optimal involvement. This study also highlights the often overlooked role of siblings in the transition process. The article recommends communication training for parents and professionals and the use of digital platforms to facilitate information sharing